Pelatihan Agro Eco-System Analysis Petani Ketela Pohon dalam Teknik Pengelolaan Organisme Pengganggu Tanaman - Sri Wahyuni; Willybrordus Lanamana; Kristono Yohanes Fowo; Lourentius Dominikus Gadi Djou; Yohanes Pande (Universitas Sebelas Maret, 2021)
Training on Agro Eco-System Analysis for Cassava Farmers in Plant Pest Organism Management Techniques. Pest population fluctuations in cassava plants tend to increase and spread rapidly in drought fields and a monoculture cropping pattern with close spacing therefore the presence of pests planted is highly dependent on agro-ecosystem conditions. Therefore ecological-based pest control is very necessary. To maintain the stability of the plant ecosystem, basic skills are needed in conducting agroecosystem analysis (AESA). Based on the analysis results obtained recommendations for appropriate ecosystem management for each growing season and facilitate farmers in determining good cultivation techniques regarding pest control, cropping patterns, soil and water conservation as well as natural enemies that are appropriate for their plants. AESA activities are carried out so that farmers understand and are skilled in managing their cassava plantations because Randotonda Village is a producer of